To study the prevalence of metabolic-associated fatty liver disease in a tertiary hospital in Bundelkhand region - Neha Rathore; Kuldeep Chandel; Ajeet Singh; Aniket Ashok Satale; Gaurav Singh (Asian Journal of Medical Sciences)
Background: Metabolic-associated fatty liver disease (MAFLD) is a growing global health concern associated with metabolic dysfunction, including obesity, type 2 diabetes mellitus, and dyslipidemia. Its prevalence is increasing, particularly in developing regions, necessitating early detection and intervention.